The relationship between service quality, price value, and website design toward E-commerce customer satisfaction among Generation-Z - Cheong, Sai Hoe; Chang, Zhi Cung; Jayesri, N.M. Rajan (2024)
There have occasionally been dips and variations in employee work performance. Due to a paucity of prior studies, other academics are beginning to pay more attention to concerns relating to employee job performance. Examining the relationship between compensation and benefits and employee performance at a few Universiti Tunku Abdul Rahman (UTAR), Kampar campus is the main goal of this study. We created 226 questionnaires for this study and gave them out to target participants who worked at Universiti Tunku Abdul Rahman (UTAR), Kampar campus. The data were analysed using SPSS software after data collection to produce the results. The final findings reveal a substantial correlation between compensation and benefits and employee performance.